Penyuluhan Pentingnya Menjaga Perilaku Hidup Bersih dan Sehat oleh Mahasiswa KKN Terpadu UMT di Kelurahan Manis Jaya Jati Uwung Kota Tangerang - Hasan, Muh; Priyo Susilo; Asep Suhendar; Hustna Dara Sarra; Ali Hanafiah Nasution; Anita Ardiyanti; Suparman Suparman; Ahmad Zaki (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
This Community Service (PKM) activity aimed to increase awareness and knowledge among the residents of Manis Jaya Village, Tangerang City, about the importance of maintaining Clean and Healthy Living Behavior (PHBS). Through a counseling session conducted by the Integrated KKN team of Universitas Muhammadiyah Tangerang, residents were encouraged to understand and apply PHBS practices, such as handwashing with soap, maintaining environmental cleanliness, and consuming healthy food. The results showed a significant increase in the residents' knowledge and healthy behaviors, although challenges like limited access to clean water and waste management facilities remain. The discussion emphasized the importance of collaboration between the government, the community, and educational institutions to ensure the sustainability of PHBS implementation. This program is expected to serve as a model for similar activities in other areas with comparable social and economic conditions. Continuous implementation and adequate infrastructure support are key to long-term success.